Diperfluorophenyl Fused Thiophene Semiconductors for n‐Type Organic Thin Film Transistors (OTFTs). (22nd June 2015) - Youn, Jangdae; Vegiraju, Sureshraju; Emery, Jonathan D.; Leever, Benjamin J.; Kewalramani, Sumit; Lou, Silvia J.; Zhang, Shiming; Prabakaran, Kumaresan; Ezhumalai, Yamuna; Kim, Choongik; Huang, Peng‐Yi; Stern, Charlotte; et al.
<x xml:space="preserve">Abstract</x> Three new fused thiophene semiconductors, end‐capped with diperfluorophenylthien‐2‐yl (DFPT) groups (DFPT‐thieno[2′, 3′:4, 5]thieno[3, 2‐b]thieno[2, 3‐d]thiophene (TTA), DFPT‐dithieno[2, 3‐b:3′, 2′‐d]thiophenes (DTT), and DFPT‐thieno[3, 2‐b]thiophene (TT)), are synthesized and characterized in organic thin film transistors. Good environmental stability of the newly developed materials is demonstrated via thermal analysis as well as degradation tests under white light. The molecular structures of all three perfluorophenylthien‐2‐yl end‐functionalized derivatives are determined by single crystal X‐ray diffraction. DFPT‐TTA and DFPT‐TT exhibit good n‐type TFT performance, with mobilities up to 0.43 and 0.33 cm2 V−1 s−1, respectively. These are among the best performing n‐type materials of all fused thiophenes reported to date. The best thin film transistor device performance is achieved via an n‐octadecyltrichlorosilane dielectric surface treatment on the thermally grown Si/SiO2 substrates prior to vapor‐phase semiconductor deposition. Within the DFPT series, carrier mobility magnitudes depend strongly on the semiconductor growth conditions and the gate dielectric surface treatment.